PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK ATAS TANAH YANG SERTIFIKAT HAK MILIKNYA DIBATALKAN OLEH PENGADILAN TATA USAHA NEGARA - Prima Risma; Darmini Roza; Philips A. Kana (LPPM Universitas Ekasakti Padang, 2023)
In human life, land is a very important need because almost all human activities take place on land. Provisions regarding land rights are regulated in Law no. 5 of 1960 concerning Basic Agrarian Regulations. Among the land rights are regarding Building Use Rights and Property Rights. And for this reason, it is necessary to register and upgrade from Building Use Rights to Property Rights. Building use rights have a limited period of time and should be upgraded to property rights in order to have legal certainty for the right holders. The increase in Building Use Rights to become permanent property rights must be registered at the Land Office where the object is located. The specification of this research is descriptive analysis. The approach used in this study is a normative-juridical approach. It is so called because this research is a literature research or document study aimed only at written regulations or other legal materials. Based on the results of the study, it shows that there is no legal protection for holders of Property Rights Certificates that have been canceled by the State Administrative Court Decision. The judge's consideration of the State Administrative Court in canceling land ownership rights is based on existing regulations and efforts made by the owner of the Certificate of Property Rights which has been canceled by the Decision of the State Administrative Court by filing an appeal.